Innovative Double H Metamaterial Structure for Amelioration in Patch Antenna Parameters - Bimal Garg; Dauood Saleem (Institute of Advanced Engineering and Science, 2013)
A rectangular microstrip patch antenna along with a SSRR based “Double H” shaped metamaterial is proposed and analyzed at a height of 3.2mm from the ground plane. This work is mainly focused on increasing the potential parameters of microstrip patch antennas. The patch antenna along with the proposed metamaterial structure is designed to resonate at 1.84GHz. The impedance bandwidth of the patch antenna along with the proposed metamaterial structure is improved by 12.9MHz and return loss is reduced by 9.89dB. All the simulation work is done by using CST-MWS Software. Double-Negative properties (Negative Permeability and Permittivity) of the proposed metamaterial structure have also been verified using Nicolson-Ross-Weir method (NRW).